Physical properties of lyocell fibers spun from isotropic cellulose dope in NMMO monohydrate - Chae, DW; Chae, HG; Kim, BC; Oh, YS; Jo, SM; Lee, WS (TEXTILE RESEARCH INST, 2002)
This article describes the physical properties of lyocell fibers spun from an isotropic cellulose spinning dope in N-methyl morpholine N-oxide (NMMO) monohydrate (IPS lyocell fibers). Wide angle x-ray diffraction (WAXD) experiments on the crimped fibers exhibit little difference in the crystal structure of IPS and Tencel lyocell fibers: both fibers reveal a cellulose II structure. However, the IPS lyocell fibers have a lower tensile modulus than Tencel by about 12.5%, although they have a similar tensile strength. Wetting and subsequent drying shift the loss tangent values higher, which is more remarkable for the IPS lyocell fibers dried under tension. Further, the IPS lyocell fibers dried under tension have a sharper alpha-transition peak than the fibers dried without tension. The IPS lyocell fibers exhibit excellent wet tensile strength: 90% of tensile strength is retained after wetting twice in distilled water. In addition, the IPS lyocell fibers show good chemical stability to acids and alkalis, except for an extremely strong alkali-pH 14. Mercerization of the IPS lyocell fibers in the buffer solution of pH 14 notably decreases the tensile modulus but increases elongation.